2013
DOI: 10.1186/1479-5876-11-292
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus-induced epithelial to mesenchymal transition in immortalized human renal proximal tubular epithelial cells: key role of heparanase

Abstract: BackgroundEverolimus (EVE) is a drug widely used in several renal transplant protocols. Although characterized by a relatively low nephrotoxicity, it may induce several adverse effects including severe fibro-interstitial pneumonitis. The exact molecular/biological mechanism associated to these pro-fibrotic effects is unknown, but epithelial to mesenchymal transition (EMT) may have a central role. Additionally, heparanase, an enzyme recently associated with the progression of chronic allograft nephropathy, coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 69 publications
3
18
0
Order By: Relevance
“…Notably, SUL alone or combined with 5 nM EVE caused the downregulation of all three EMT markers. On the contrary, a high concentration EVE (100 nM) was able to significantly upregulate all genes encoding for the three mesenchymal markers (confirming our previous published results [24]). However, the co-treatment with SUL reversed the pro-fibrotic effects induced by the high dose of EVE.…”
Section: Effects Of Eve and Sul (Alone Or In Combination) On Gene-andsupporting
confidence: 90%
“…Notably, SUL alone or combined with 5 nM EVE caused the downregulation of all three EMT markers. On the contrary, a high concentration EVE (100 nM) was able to significantly upregulate all genes encoding for the three mesenchymal markers (confirming our previous published results [24]). However, the co-treatment with SUL reversed the pro-fibrotic effects induced by the high dose of EVE.…”
Section: Effects Of Eve and Sul (Alone Or In Combination) On Gene-andsupporting
confidence: 90%
“…6,7,11 Epithelial to mesenchymal transition (EMT), a phenotypic conversion of epithelium to a fibroblastic or myofibroblastic phenotype, induced by suppression of the Akt protein kinase signaling pathway, may play a central role in the mTOR inhibitor-associated profibrotic process. 10 Masola and associates 10 recently demonstrated that high concentrations of everolimus induced an up-regulation of all EMT markers in human renal epithelial proximal tubular cells, including alpha-smooth muscle actin, vimentin, fibronectin, and matrix metalloproteinase 9, at both the gene and protein levels. The promotion of EMT may be facilitated 10 or not 12 by a transforming growth factor β-dependent mechanism and appears to be mediated through a heparanase-stimulating process 10 known to be involved in the pathogenesis of several proteinuric nephropathies.…”
Section: Case Discussion and Review Of The Literaturementioning
confidence: 99%
“…10 Masola and associates 10 recently demonstrated that high concentrations of everolimus induced an up-regulation of all EMT markers in human renal epithelial proximal tubular cells, including alpha-smooth muscle actin, vimentin, fibronectin, and matrix metalloproteinase 9, at both the gene and protein levels. The promotion of EMT may be facilitated 10 or not 12 by a transforming growth factor β-dependent mechanism and appears to be mediated through a heparanase-stimulating process 10 known to be involved in the pathogenesis of several proteinuric nephropathies. 13,14 In contrast, low dose of everolimus, commonly used during organ transplant, failed to induce EMT in the same experimental settings.…”
Section: Case Discussion and Review Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations